2010
DOI: 10.1007/s00128-010-9939-6
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and Cadmium Contamination of Irrigation Water, Sediment, Soil and Shallow Groundwater in a Wastewater-Irrigated Field in Tianjin, China

Abstract: We investigated the concentrations of Hg, Cd, Pb and As in samples of irrigation water, sediment, soil and groundwater from a field in Tianjin that was irrigated with wastewater. The results showed that the concentrations (Hg, 0.82 microg/L; Cd, 0.18 microg/L; Pb, 1.5 microg/L; As, 8.02 microg/L) in the irrigation water did not exceed the China Surface Water Quality Standard or the maximum concentrations in irrigation water recommended by the FAO. The concentrations of metals in the groundwater of wells (Hg, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…Wang primarily attributed that pollution to the use of wastewater for irrigation, and proposed that the most contaminated farmland had also been treated with sewage sludge. The observations of Dong et al (2001) are consistent with those of others Hu et al, 2006;Li et al, 2008c;2009b;Liu et al, 2007d;Song et al, 2006b;Wang and Lin, 2003;Wang and Tao, 1998;Wu and Cao, 2010;Zhuang et al, 2009).…”
Section: Downloaded By [Florida Atlantic University] At 01:02 20 Septsupporting
confidence: 92%
See 1 more Smart Citation
“…Wang primarily attributed that pollution to the use of wastewater for irrigation, and proposed that the most contaminated farmland had also been treated with sewage sludge. The observations of Dong et al (2001) are consistent with those of others Hu et al, 2006;Li et al, 2008c;2009b;Liu et al, 2007d;Song et al, 2006b;Wang and Lin, 2003;Wang and Tao, 1998;Wu and Cao, 2010;Zhuang et al, 2009).…”
Section: Downloaded By [Florida Atlantic University] At 01:02 20 Septsupporting
confidence: 92%
“…Their findings were corroborated by Khan et al (2008), who reported that lead concentrations in six vegetables grown in soils irrigated with wastewater in Beijing ranged from 2.6-4.5 μg/g (dry weight), which was significantly higher than the concentrations of those crops grown in a reference soil. Cao and Ikeda (2000) and Wu and Cao (2010), likewise, found similar elevations of lead and other metal concentrations in soils and sediments that had received applications of wastewater sludge in Tianjin. In response to such contamination problems, Sun et al (2009b) investigated the potential of a hyperaccumulator plant (Sedum alfreddi Hance) to bioremediate lead and other pollutants from agricultural soils contaminated by industrial wastewater irrigation.…”
Section: Lead Contamination From Sewage and Sludge Applicationssupporting
confidence: 59%
“…All sediment samples collected from the BR exceeded background and environmental guideline levels suggesting that industrial effluents from the Tianjin region represented a significant source of Hg in the BR. Although large point-source discharges of wastewater containing mercury have been detected (Wu and Cao 2010), mercury pollution still persisted in this area due to high THg emissions from other mercury releasing activities. There were two spikes of THg concentrations in the sediments: one was at the headstream (BR-S1); the other one was at middle and downriver area (BR-S6).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, contaminated soils can enhance the release of metals and uptake of contaminant metals by plants and pose a risk to human health due to trophic transfer through the food chain (Zhou et al 2015). While wastewater irrigation plays an important role in metal contamination of local soils and agricultural products (Gupta et al 2008;Wu and Cao 2010;López-Blanco et al 2015). Long-term irrigation with sewage effluent has been shown an increasement of the amount and availability of metals in agricultural soils (Bhattacharyya et al 2008).…”
mentioning
confidence: 99%
“…Jalali et al ( 2008 ) showed in Iran that if wastewater was applied to soil for a long enough period, leaching concentrations will reach groundwater at elevated levels. Wu and Cao ( 2010 ) informed that concentrations of metals in groundwater from wells were lower than the China Groundwater Quality Standard and the WHO guideline values for drinking water, but a substantial build up of Hg and Cd in river sediments and wastewater-irrigated soils was observed. During long-term sewage irrigation, principal component analysis for organ chlorine pesticides (OCPs) content in groundwater in China showed that the occurrence and distribution of OCPs in groundwater systems can mainly be attributed to the infl uence of fl ow fi eld of groundwater and also to the current pesticide use (Zhang et al 2013 ).…”
Section: Groundwatermentioning
confidence: 99%